Review of magnetic nanostructures grown by focused electron beam induced deposition (FEBID). (17th May 2016) - De Teresa, J M; Fernández-Pacheco, A; Córdoba, R; Serrano-Ramón, L; Sangiao, S; Ibarra, M R
Abstract: We review the current status of the use of focused electron beam induced deposition (FEBID) for the growth of magnetic nanostructures. This technique relies on the local dissociation of a precursor gas by means of an electron beam. The most promising results have been obtained using the Co2 (CO)8 precursor, where the Co content in the grown nanodeposited material can be tailored up to more than 95 at.%. Functional behaviour of these Co nanodeposits has been observed in applications such as arrays of magnetic dots for information storage and catalytic growth, magnetic tips for scanning probe microscopes, nano-Hall sensors for bead detection, nano-actuated magnetomechanical systems and nanowires for domain-wall manipulation. The review also covers interesting results observed in Fe-based and alloyed nanodeposits. Advantages and disadvantages of FEBID for the growth of magnetic nanostructures are discussed in the article as well as possible future directions in this field.